Bioengineering the coral holobiont : Evidence, hurdles, and pathways for rebuilding reefs - Peixoto, Raquel S.; Alker, Amanda; Voolstra, Christian R. (My University, 2025)
At the frontline of climate impacts, coral reef ecosystemswill likely not persist in a functional state without targeted management and intervention approaches. Bioengineering the coral holobiont, comprising the cnidarian animal host, algal symbionts, and the remaining microbiome, offers promise for enhancing resilience but faces significant scientific, ecological, and governance challenges. We propose strategic, evidence-based pathways to responsibly integrate bioengineering into coral restoration and conservation.
Keywords: 570